“What are nurses‟ perspectives of a good death and how does this impact patient care?” - Woollard, Sally (2012)
This dissertation aims to answer the research question “What are nurses‟ perspectives of a good death and how does this impact patient care?” The dissertation takes the form of a critical literature review, which is explained in the methodology chapter. A background to the concept of a good death is provided, as well as definitions of palliative care and end of life care. The differences between primary and secondary care nurses‟ perspectives arouse as a theme of interest from the literature. The studies reviewed were used to synthesise a set of perspectives for both primary and secondary care nurses. The primary care nurses‟ perspectives of a good death found were; respecting patient choice, symptom management, meeting spiritual and emotional needs, the presence of loved ones who can provide care, the availability of good resources, good communication, good organisation, patient remains at home, the death is accepted and there are good inter-professional relationships between those involved in the care. The secondary care nurses‟ perspectives of a good death found were; symptom management, preparing for death, providing palliative care, good decisions from doctors, patient understanding, respecting patient choice, good practice, the death not being medicalised and there being enough staff. These themes have been discussed and compared, and causes for the differences suggested. The themes unique to nurses have also been discussed. The potential impact these ideas may have on practice has been discussed. The dissertation concludes by acknowledging the unavoidable limitations of the research, and suggesting implications for future practice and research.